2015
DOI: 10.1002/app.42625
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of galactosylated chitosan–5‐fluorouracil acetic acid based nanoparticles for controlled drug delivery

Abstract: In this study, a novel type of macromolecular prodrug, N-galactosylated chitosan (GC)25-fluorouracil acetic acid (FUA) conjugate based nanoparticles, was designed and synthesized as a carrier for hepatocellular carcinoma drug delivery. The GC-FUA nanoparticles were produced by an ionic crosslinking method based on the modified ionic gelation of tripolyphosphate with GC-FUA. The structure of the as-prepared GC-FUA was characterized by Fourier transform infrared and 1 H-NMR analyses. The average particle size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…The preparation of the GC-FUA-NPs followed the established procedure, which has been described in detail elsewhere (Yu et al, 2015 ). The compound (GC-FUA) was synthesized by amide condensation reaction of GC and FUA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of the GC-FUA-NPs followed the established procedure, which has been described in detail elsewhere (Yu et al, 2015 ). The compound (GC-FUA) was synthesized by amide condensation reaction of GC and FUA.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the in vitro cytotoxicity and cellular uptake, in vivo pharmacokinetic (PK) and tissue distribution of GC-FUA nanoparticles also were investigated in this research (our laboratory has been preparing a novel macromolecular prodrug N-galactosylated-chitosan-5-fluorouracil acetic acid (GC-FUA) conjugate based nanoparticle; Yu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…All the prepared specimens demonstrated bands at 1649, 810, and 496 cm −1 due to Si–O bending and stretching, respectively. Contrasted and chitosan (Murali et al., 2018 ), Figure 1(b,c) demonstrates the bands of amides I and II of GC exhibited at the peak ranges of 1626 and 1531 cm −1 , indicating that bathochromic move, which revealed that MONPs was covered by the GCS (Yu et al., 2015 ). Additionally, an extra band displays in the MONPs@RV and GCS-MONPs@RV at 1580 cm −1 because of the amide bowing which is missing in GCS-MONPs.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been discovered that transfecting miR-122 mimics into HCC mice using cationic lipid nanoparticles as carriers could highly target HCC cells, inhibiting proliferation and angiogenesis. The use of natural macromolecular nanoparticles as vectors to deliver both ncRNAs and antineoplastic agents in HCC therapy has been studied previously [90] . Clinical data have shown that miR-21 in HCC cell lines and clinical HCC samples was a significant modulator of the anti-tumor effect of interferon-alpha (IFN-α) and 5-fluorouracil (5-FU).…”
Section: Mirna-related Intervention and Therapy Of Hccmentioning
confidence: 99%